Relationship between the elimination of the age limit as a ground for cessation and the quality of university teaching in the UNMSM faculty of education - Quispe Cárdenas, Hilda Rosa (2023)
University higher education in Peru has been significantly transformed since the promulgation of the University Law in 2014, establishing new purposes and functions for universities and placing the Ministry of Education as the governing body of educational policy in order to improve the quality. One of the measures, which the previous law already contemplated, regarding the career of university teachers, was to establish as one of the grounds for dismissal having reached 70 years of age, a provision that was later modified by setting the age limit as 75 years old, until, finally, a new modification was made, eliminating the age limit as a cause for termination. With this measure, university professors continue to carry out their work as long as they maintain their physical and mental health, verifying this through medical examinations. Likewise, there is no age limit for starting a teaching career. With this, generational change is limited, making it difficult for new teachers to enter, as well as their possibilities of pursuing a career and holding positions at the university.